2019
DOI: 10.1101/gr.245332.118
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally induced plasticity of programmed DNA elimination boosts somatic variability inParamecium tetraurelia

Abstract: Can ecological changes impact somatic genome development? Efforts to resolve this question could reveal a direct link between environmental changes and somatic variability, potentially illuminating our understanding of how variation can surface from a single genotype under stress. Here, we tackle this question by leveraging the biological properties of ciliates. When Paramecium tetraurelia reproduces sexually, its polyploid somatic genome regenerates from the germline genome through a developmental process tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 58 publications
6
48
0
Order By: Relevance
“…Alternatively, somatic IESs may have accrued preferentially in down-regulated genes. At any rate, the negative scaling between IES retention levels and gene expression in both the control stock d12 (Vitali et al 2019) and stock 51 (Kendall’s τ = −0.176, P <0.0001) further supports the relationship between developmental variation and somatic gene expression in P. tetraurelia .…”
Section: Resultsmentioning
confidence: 62%
See 4 more Smart Citations
“…Alternatively, somatic IESs may have accrued preferentially in down-regulated genes. At any rate, the negative scaling between IES retention levels and gene expression in both the control stock d12 (Vitali et al 2019) and stock 51 (Kendall’s τ = −0.176, P <0.0001) further supports the relationship between developmental variation and somatic gene expression in P. tetraurelia .…”
Section: Resultsmentioning
confidence: 62%
“…It also predicts that the MA lines and the control stocks may have undergone divergent changes in gene expression level over the ∼4-year long MA experiment. To test this, we leveraged the transcriptomes of the control stocks 51 (Arnaiz et al 2017) and d12 (Vitali et al 2019) obtained at standard (MA experiment-like) cultivation conditions. We found that genes with reduced levels of expression in the control stocks preferentially accumulate somatic IESs ( Figure 3D ), consistent with previous reports (Arnaiz et al 2012; Ferro et al 2015; Vitali et al 2019) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations